Investigation of Atrazine Sorption to Biochar With Titration Calorimetry and Flow-Through Analysis: Implications for Design of Pollution-Control Structures - Penn, Chad J.; Gonzalez, Javier M.; Chagas, Isis (Frontiers in Chemistry, 2018)
Atrazine is one of the most common broad-leaf herbicides used in the world. However, due to extensive use for many years, atrazine often appears in surface and groundwater. Atrazine transport is inhibited by degradation or sorption to soil components, especially organic matter. Biochar is a charcoal-like material produced from pyrolysis of biomass. Due to the amount and type of functional groups found on biochar, this product has shown potential for sorption of atrazine from solution. There is an interest in developing best management practices utilizing biochar to filter atrazine from non-point drainage with pollution-control structures such as blind-inlets. The objective of this study was to explore the kinetics and thermodynamics of atrazine sorption to biochar using two different approaches: flow-through sorption cells and isothermal titration calorimetry (ITC). 25 mg of an oak (Quercus spp)-derived biochar was suspended in water and titrated twenty-five times (0.01 mL per titration) with atrazine at three different concentrations, and by a single titration (0.25 mL), with heat of reaction directly measured with ITC. A benchtop atrazine sorption study that simulated the titration experiment was also conducted. A continuous flow-through system was used to quantify the impact of contact time on atrazine sorption to biochar. Atrazine sorption to biochar displayed both exothermic and endothermic signals within each titration, although the net reaction was exothermic and proportional to the degree of sorption. Net enthalpy was 4231 kJ mole-1 atrazine sorbed. The existence of both exotherms and endotherms within a single titration, plus observation of an initial fast reaction phase from 0-300 seconds followed by a slower phase, suggested multiple sorption mechanisms to biochar. Results of flow-through tests supported kinetics observations, with the 300-sec contact time removing much more atrazine compared to 45 sec, while 600 sec improved little compared to 300 sec. Based on flow-through results, annual atrazine removal goal of 50%, and typical Midwestern U.S. tile drainage conditions, a pollution-control structure implementing this biochar sample would require 32 and 4 Mg for a design utilizing a contact time of 45 and 300 seconds, respectively. Future work is necessary for estimating degradation of atrazine sorbed to biochar.